A Comparative Perspective on Citizenship and Sustainability Education in Armenia, Germany, Iran and Tanzania - Julia Hufnagl; Joseph Badokufa Bulugu; Hamed Ghaderinezhad; Heribert Hinzen; Balázs Németh; Emma Yarazyan (AS: Andragoška Spoznanja)
The objective of this article is to respond to the question of how providers, programmes, participants, and locations play a pivotal role in Education for Sustainable Development (ESD) and Global Citizenship Education (GCE) in Armenia, Germany, Iran and Tanzania. To this end, a comparative international approach is employed, utilising the following categories: (1) providers, (2) programmes, (3) participants, and (4) locations. ESD and GCE are two transformative educational models highlighted by Sustainable Development Goal 4.7. They aim to equip individuals with the knowledge and values necessary to address global challenges such as environmental degradation and social inequalities. Our findings indicate that the categories both individually and collectively signal and resonate choices and limitations to ESD- and GCE-related adult learning activities, which have been significantly influenced by both global and macro level initiatives and local, regional realities.